MAHMUDKHODZHI BEKHBUDY AND HIS ANALYTICAL BIOGRAPHY - SHARIPOVA , GUZAL; ODILOVA , MUSLIMA (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article presents a critical analysis of the life and socio-political activities of the outstanding leader of Turkestan Jadidism, Mahmudkhodzhi Bekhbudy (1875–1919). Unlike traditional historical reviews, this study uses a socio-psychological approach to examine the evolution of his educational views. The focus is on three key aspects, the formation of cognitive dissonance in childhood when bookish ideals collided with the realities of colonial society; mature institutional activity to transform education, the press and literature; and strategic miscalculations and weaknesses in his political doctrine. The analysis shows that Behbudi’s tragedy lay in radically outpacing the level of development of the masses, his reformist pace gave rise to internal resistance from traditional society, and his political idealism proved defenceless in the face of violence during the period of instability after 1917.